2021
DOI: 10.3390/antiox10050735
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Associated with ROS-Dependent Angiogenesis in Lower Extremity Artery Disease

Abstract: Currently, atherosclerosis, which affects the vascular bed of all vital organs and tissues, is considered as a leading cause of death. Most commonly, atherosclerosis involves coronary and peripheral arteries, which results in acute (e.g., myocardial infarction, lower extremities ischemia) or chronic (persistent ischemia leading to severe heart failure) consequences. All of them have a marked unfavorable impact on the quality of life and are associated with increased mortality and morbidity in human populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 145 publications
(193 reference statements)
1
11
0
Order By: Relevance
“…Recent studies indicated a diabetic foot ulcers prevalence of 11.6% while venous and pressure ulcers affect 1–3% of the total population which are expected to rise in tandem with the aging population, low body mass index, and prolonged illness [ 34 , 35 ]. Arterial ulcers or peripheral artery disease (PAD) are associated with the occlusion of lower limb arteries, and advanced atherosclerosis (calcification and stenosis) and cause critical limb ischemia, tissue necrosis, and persistent inflammation [ 36 ]. The severity of chronic conditions of PAD increases with metabolic disease prevalence and is correlated to inflammation (for example, C-reactive protein) and fibrosis (for example, galectin-3) biomarkers [ 37 , 38 ].…”
Section: Wounds and The Wound Healing Processmentioning
confidence: 99%
“…Recent studies indicated a diabetic foot ulcers prevalence of 11.6% while venous and pressure ulcers affect 1–3% of the total population which are expected to rise in tandem with the aging population, low body mass index, and prolonged illness [ 34 , 35 ]. Arterial ulcers or peripheral artery disease (PAD) are associated with the occlusion of lower limb arteries, and advanced atherosclerosis (calcification and stenosis) and cause critical limb ischemia, tissue necrosis, and persistent inflammation [ 36 ]. The severity of chronic conditions of PAD increases with metabolic disease prevalence and is correlated to inflammation (for example, C-reactive protein) and fibrosis (for example, galectin-3) biomarkers [ 37 , 38 ].…”
Section: Wounds and The Wound Healing Processmentioning
confidence: 99%
“…The heart is essential for life, but it has limited regenerative capacity in the adult and decreased extent of microvasculature can have serious and irreversible consequences like heart failure (HF). Given these factors, the whole complex process of neovascularization [14] taking place within the heart tissue is so crucial to understanding. Moreover, because the myocardium itself could serve as a source of treatment, via resident cardiac progenitor cells [15] therefore generation of new blood vessels for delivery oxygen and nutrients to newly created cells is necessary for proper cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis (AS) involves the coronary and peripheral arteries and can have consequences such as ischemia of the lower limbs and myocardium, or chronic heart failure ( 1 ). Atherothrombosis represents the terminal manifestation of this pathology.…”
Section: Introductionmentioning
confidence: 99%